EFFECT OF IRON ON THE GROWTH AND YIELD CONTRIBUTING PARAMETERS OF WHEAT (TRITICUM AESTIVUM L.) - G. Abbas; M. Q. Khan; M. J. Khan; F. Hussain; I. Hussain (Journal of Animal and Plant Sciences, 2009)
Field experiments were conducted at Government Adaptive Research Farm Karor Lal Eason, district- Layyah, to study the impact of trace elements on uptake of nitrogen, phosphorus, potassium and yield of wheat. The experiments were laid out in RCBD having three replications. Soil samples were collected before sowing of crop from 0-15 cm depth and analyzed for physical and chemical properties (texture, pH, ECe, soluble, anions cations, soil organic matter, NPK, Zn, Fe and Mn). Wheat variety Bhakkar-2002 was sown during Rabi season 2005-2006 and 2006-2007. The recommended doses of N, P and K were applied @ 150:100:60 kg N:P2O5:K2O ha-1, through broadcast at the time of sowing while N was applied in two equal doses after 25 days and 40 of sowing at the time of irrigation. Micronutrient, i.e. Fe was applied @ 0, 4, 8, 12 and 16 kg ha-1 alone as well as combined in a same trial, in the form of Iron sulphate at the time of sowing. Results showed that application of recommended NPK fertilizer significantly increased all parameters of wheat, i.e. Plant height, spike length (cm), number of spikelets spike-1, number of fertile tillers m-2 straw yield, grain yield and 1000-grain weight, significantly over control (no NPK). Application of Fe also showed a significant response to wheat at lower rates. High rates of Fe reduced/ did not effect the growth and yield contributing parameters of crop. The best results were obtained when applied Fe @ 12 Kg ha-1 with recommended NPK. Increasing rates of Fe dose up to 12 kg ha-1 increased grain yield while higher rate did not have any significant effect.
Keywords: Trace element (Fe); NPK fertilizer; wheat (Triticum aestivum L.); Pakistan